Dose‐dependent induction of CYP3A activity by St. John's wort alone and in combination with rifampin - Nicolas Hohmann; Anna S. Friedrichs; Jürgen Burhenne; Antje Blank; Gerd Mikus; Walter E. Haefeli (Wiley, 2024)
Abstract The dose dependence of the effect of enzyme inducers and the effect of the combined administration of two inducers that exert their effect via the same induction pathway (pregnane X receptor) have not been well studied. Using oral midazolam microdoses (30 μg), we have investigated CYP3A4 induction by St. John's wort (SJW) in 11 healthy volunteers using low (300 mg/day containing 7.48 mg hyperforin), therapeutic (900 mg/day), and supratherapeutic doses of SJW (1800 mg/day) for 14 days. SJW was then co‐administered with rifampin (600 mg/day) for a further 7 days to evaluate the effect of the combined administration of two inducers. In addition, intravenous midazolam microdoses (10 μg) were administered before SJW, at SJW 1800 mg/day, and during administration of the two inducers to assess the hepatic contribution to total induction (semi‐simultaneous administration). Administration of SJW increased oral midazolam clearance 1.96‐fold (300 mg/day), 3.86‐fold (900 mg/day), and 5.62‐fold (1800 mg/day), and 17.5‐fold after the addition of rifampin. Concurrently, the clearance of intravenous midazolam increased 2.05‐fold (1800 mg/day) and 2.93‐fold (SJW + rifampin). These results show that rifampin significantly enhances the induction of the highest SJW doses both hepatically and overall and suggest that these metabolic effects occur predominantly in the gut. These findings also suggest that in drug interactions involving strong and moderate enzyme inducers, the perpetrator effects of the strong inducer are decisive for the interaction.